Pharmacological Stimulation of Type 5 Adenylyl Cyclase Stabilizes Heart Rate Under Both Microgravity and Hypergravity Induced by Parabolic Flight - Yunzhe Bai; Takashi Tsunematsu; Qibin Jiao; Yoshiki Ohnuki; Yasumasa Mototani; Kouichi Shiozawa; Meihua Jin; Wenqian Cai; Hui-Ling Jin; Takayuki Fujita; Yasuhiro Ichikawa; Kenji Suita; et al. (Journal of Pharmacological Sciences, 2012)
We previously demonstrated that type 5 adenylyl cyclase (AC5) functions in autonomic regulation in the heart. Based on that work, we hypothesized that pharmacological modulation of AC5 activity could regulate the autonomic control of the heart rate under micro- and hypergravity. To test this hypothesis, we selected the approach of activating AC5 activity in mice with a selective AC5 activator (NKH477) or inhibitor (vidarabine) and examining heart rate variability during parabolic flight. The standard deviation of normal R-R intervals, a marker of total autonomic variability, was significantly greater under micro- and hypergravity in the vidarabine group, while there were no significant changes in the NKH477 group, suggesting that autonomic regulation was unstable in the vidarabine group. The ratio of low frequency and high frequency (HF) in heart rate variability analysis, a marker of sympathetic activity, became significantly decreased under micro- and hypergravity in the NKH477 group, while there was no such decrease in the vidarabine group. Normalized HF, a marker of parasympathetic activity, became significantly greater under micro- and hypergravity in the NKH477 group. In contrast, there was no such increase in the vidarabine group. This study is the first to indicate that pharmacological modulation of AC5 activity under micro- and hypergravity could be useful to regulate the autonomic control of the heart rate. Keywords:: adenylyl cyclase isoform, autonomic nerve activity, parabolic flight, heart rate variability, microgravity